Degradation of 1,2,3-trichloropropane by unactivated persulfate and the implications for groundwater remediation - Liu, Shuyu; Gu, Chunyun; Zhang, Jiaxin; Luo, Chaoyi; Rong, Xun; Yue, Gangsen; Liu, Hanyu; Wen, Jing; Ma, Jie (The Science of the total environment, 2023)
Persulfate (PS) is widely used as an in situ chemical oxidation (ISCO) technology for groundwater and soil remediation. While conventional theory generally assumes that PS needs to be “activated” to produce reactive radicals for pollutant degradation, herein, PS without explicit activation system was discovered for the degradation of 1,2,3-TCP with the generation of reactive oxidation species (ROS). Comparison of five common ISCO oxidants (PS, peroxymonosulfate, hydrogen peroxide, potassium permanganate, and sodium percarbonate) indicated that only unactivated PS was able to degrade 1,2,3-TCP in both pure water and 12 natural water samples. 50 μM 1,2,3-TCP degradation can be continued as long as there is enough PS (50 mM). The degradation rate of 1,2,3-TCP increased 450 % when the PS concentration increased from 10 mM to 50 mM and 500 % when the temperature increased from 25 °C to 45 °C. Electron paramagnetic resonance (EPR) analyzes, hydroxyl radicals (·OH) probe reaction and radical quenching experiments confirmed the involvement of both sulfate radicals (SO4·-) and ·OH that were responsible for 1,2,3-TCP degradation and ·OH played a more important role. HCO3−, Cl− and NOM are three groundwater matrix species that are most likely to inhibit PS oxidation of 1,2,3-TCP. Compared to activated PS, unactivated PS is more promising and more practical for groundwater remediation, since it has several advantages: (1) longer lifetime and better long-term availability; (2) ability of enduring contaminant degradation; (3) applicable for low-permeability zones remediation and potential to alleviate contaminant rebound or tailing problems; (4) environmental friendly; and (5) lower cost. Overall, results of this study show that unactivated PS is a promising in situ remediation technology that may be a good candidate for the most challenging low permeable zone remediation. [Display omitted] •Without additional activator, PS can effectively degrade 1,2,3-TCP in various water samples.•·OH and SO4·- are responsible for 1,2,3-TCP degradation by PS without explicit activation.•50 μM 1,2,3-TCP degradation can be continued as long as there is enough PS (50 mM).•Unactivated PS is a good candidate for the low permeable zone remediation.